Construction and application of multi-scale 3D geological models: an example from Qingdao City, China - Ji, Dong; Hou, Jing; Cheng, Zhiliang; Wei, Shuai; Zhai, Yue; Li, Wenhao (Frontiers in Earth Science, 2024)
The 3D geological model serves as a cornerstone, establishing the essential foundation and prerequisite for numerical simulations, analytical assessments, and evaluative procedures that are integral to the disciplines of geotechnical and geological engineering. The task of integrating vast quantities of multi-source, heterogeneous modeling data, the absence of stratigraphic division standards to meet varying precision requirements, and addressing the application demands of 3D geological models beyond the geological domain, pose significant challenges to the endeavor of 3D geological modeling. This is especially true for the construction of large-scale, high-precision 3D geological models at the urban level. Our research introduces a methodology for 3D geological modelling, with a particular focus on the dual-weighted interpolation technique for the integration of land-sea data and the establishment of a three-tiered coding system for bedrock layers. Focusing on Qingdao, a city characterized by its bedrock geology and situated along the eastern coastal region of China, our proposed method has successfully catalyzed the creation of models across four distinct scales: a comprehensive city-wide model covering an area of 11,282 square kilometers, five general models, two demonstration models, and five refined models. Further application cases have demonstrated that these models are not only capable of meeting the requirements of geological and geotechnical engineering across various scenarios, but also exhibit excellent interoperability and significant application potential when integrated with Building Information Modeling (BIM), Geographic Information Systems (GIS), and Internet of Things (IoT) technologies. The outcomes of this study are significant for the theoretical development and technological advancement of 3D geological modeling, and can also bring inspiration and reference to the work of 3D geological modeling in other areas.